2014
DOI: 10.1063/1.4902315
|View full text |Cite
|
Sign up to set email alerts
|

High internal quantum efficiency ultraviolet to green luminescence peaks from pseudomorphic m-plane Al1−xInxN epilayers grown on a low defect density m-plane freestanding GaN substrate

Abstract: Articles you may be interested inHomoepitaxial AlN thin films deposited on m-plane ( 1 1 ¯ 00 ) AlN substrates by metalorganic chemical vapor deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
62
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(76 citation statements)
references
References 58 publications
13
62
1
Order By: Relevance
“…The notation in Figure and indicates the number of SL layers, m / n . Experimental values for AlInN alloys are shown for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The notation in Figure and indicates the number of SL layers, m / n . Experimental values for AlInN alloys are shown for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Bandgaps of Al 1− x In x N alloys and m InN/ n AlN SLs as a function of In content x . Experimental data for AlInN alloys are shown for comparison …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, since the growth of high‐quality crystal is herculean, Al 1− x In x N alloys have never been used as light‐emitting media, although their bandgap energies ( E g ) cover full spectrum from UV‐C to near‐infrared (IR) wavelengths. Here, we demonstrate planar vacuum fluorescent display (VFD) devices emitting polarized UV‐C, blue, and green light using m ‐plane oriented Al 1− x In x N 3D epitaxial nanostructures, which are composed of a dense array of ≈50 nm thick nanoboards. The results of positron annihilation spectroscopy (PAS) measurement revealed that the concentration of Al vacancies (V Al ), [V Al ], in all samples are at the lowest of 10 19 cm −3 .…”
mentioning
confidence: 99%
“…In the literature, there are only very few reports on the growth and characterization of m ‐plane AlInN , most of which are dealing with growth of m ‐plane AlInN on ZnO‐substrates. For AlInN lattice‐matched to the a ‐axis of m ‐GaN substrates, Durand et al observed the strain‐driven formation of cracks along the c ‐direction ().…”
Section: Introductionmentioning
confidence: 99%